Application of CHSE at 101 Hotel Malang - Dena Dwitia, Daneswara Ezra; Sutanto, Dewi Hermin; Astuti, Widji; Anam, Mochammad Musafaul; Risfandini, Andini (Jurnal Pariwisata Tourista, 2022)
This study discusses the application of CHSE at Hotel 101 Malang. The COVID-19 pandemic that has hit the world has caused changes in the behavior of the world community in traveling or traveling. One way to survive this pandemic is to adapt to new habits. To meet these needs, the government created a program called CHSE certification. CHSE stands for Cleanliness, Health, Safety, and Environmental Sustainability in Indonesian which means Cleanliness, Health, Safety, and Environmental Sustainability. This research takes the object of Hotel 101 Malang because Hotel 101 Malang is one of the well-known five-star hotels in Malang. The method used is descriptive qualitative method. The benefit of this research is to get the results that Hotel 101 Malang has met the CHSE standard and received a CHSE certificate, so it can be said that Hotel 101 Malang has implemented CHSE which is expected to increase public confidence in choosing accommodation during the pandemic.